2022
DOI: 10.5812/semj.113673
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Povidone-iodine Versus Chlorhexidine for Periurethral Cleaning Before Catheterization on Pyuria and Bacteriuria Among Emergency Department Patients

Abstract: Background: We aimed to determine the effect of periurethral cleaning before catheterization using chlorhexidine and povidone-iodine on bacteriuria and pyuria. Methods: This study was a single-blind clinical trial on a sample selected by convenience sampling. Demographic and clinical questionnaires were completed, and patients were randomly divided into two groups) 36 patients each of povidone-iodine and chlorhexidine using Minimization Software based on confounding variables including age, consciousness level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
2
0
Order By: Relevance
“…The chlorhexidine was the most efficient in hand antisepsis than other products, such as povidone-iodine (Figure 1). Some studies have shown that there are no differences between povidone and chlorhexidine in terms of effectiveness in reducing the bacterial flora of the skin; however, povidoneiodine has iodine-related clinical risks; it is more expensive, and the period of action is reduced in the presence of organic compounds [88]. On the other hand, chlorhexidine does not lose its effectiveness when exposed to blood and has a longer disinfecting effect on the skin, so it is often used for hand washing, and has shown lower rates of surgical infection [88][89][90].…”
Section: Discussionmentioning
confidence: 99%
“…The chlorhexidine was the most efficient in hand antisepsis than other products, such as povidone-iodine (Figure 1). Some studies have shown that there are no differences between povidone and chlorhexidine in terms of effectiveness in reducing the bacterial flora of the skin; however, povidoneiodine has iodine-related clinical risks; it is more expensive, and the period of action is reduced in the presence of organic compounds [88]. On the other hand, chlorhexidine does not lose its effectiveness when exposed to blood and has a longer disinfecting effect on the skin, so it is often used for hand washing, and has shown lower rates of surgical infection [88][89][90].…”
Section: Discussionmentioning
confidence: 99%